Ca2+-Permeable Channels/Ca2+ Signaling in the Regulation of Ileal Na+/Gln Co-Transport in Mice - Chu, Fenglan; Wan, Hanxing; Xiao, Weidong; Dong, Hui; Lü, Muhan (Frontiers in Pharmacology, 2022)
Oral glutamine (Gln) has been widely used in GI clinical practice, but it is unclear if Ca2+ regulates intestinal Gln absorption although both of them are essential nutrients for mammals. Ussing chambers were used to determine Gln (25 mM)-induced Isc through Na+-Gln cotransporters in small intestine in the absence or the presence of selective activators or blockers of ion channels and transporters. Luminal but not serosal application of Gln induced marked intestinal Isc, especially in the distal ileum. Ca2+ removal from both luminal and serosal sides of the ileum significantly prevented Gln absorption. Blocking either luminal Ca2+ entry via the voltage-gated calcium channels (VGCC) or endoplasmic reticulum (ER) release via inositol 1,4,5-triphosphate receptor (IP3R) and ryanodine receptor (RyR) attenuated the Gln-induced ileal Isc, Likewise, blocking serosal Ca2+ entry via the store-operated Ca2+ entry (SOCE), TRPV1/2 channels and Na+/Ca2+ exchangers (NCX) attenuated the Gln-induced ileal Isc, In contrast, activating TRPV1/2 channels enhanced the Gln-induced ileal Isc, We concluded that Ca2+ signaling is critical for intestinal Gln absorption and multiple plasma membrane Ca2+-permeable channels and transporters play roles in this process. The Ca2+ regulation of ileal Gln absorption expand our understanding of intestinal nutrient uptake and may have significance in GI health and disease.